Effectiveness of interactive health dialogue in improving knowledge of cervical cancer screening among women in rural Nigerian communities - Zibima, Soupriye B.; George, Boma I.; Dambo, Jane E.; Moses, Eunice B. (International Journal Of Community Medicine And Public Health, 2025)
Background: Cervical cancer (CC) remains a growing public health problem, especially in developing countries like Nigeria, where the uptake of CC screening is low. Limited knowledge about screening contributes to this low uptake. This study examined the effectiveness of an interactive health dialogue (IHD) in improving knowledge of CC screening among women in rural Nigerian communities. Methods: A one group pre-test post-test interventional study was conducted among 50 women of reproductive age in selected rural communities of Nigeria. Participants were selected using a multistage sampling technique. Data were collected using a structured interviewer-administered questionnaire before and after the intervention. Descriptive statistics summarized sociodemographic characteristics and knowledge scores, while paired t-tests assessed the intervention's impact. Chi-square tests explored relationships between age and knowledge. Results: The mean age of respondents was 42±6.2 years, with most respondents (44.0%) married and 78.0% identifying as Christians. At baseline, 82.0% of respondents had low knowledge of CC screening, with only 18.0% knowing its causative organism. Post-intervention, 84.0% had high knowledge scores, indicating a significant improvement in knowledge (p=0.000). The chi-square analysis revealed no significant relationship between age and knowledge (X²=11.412, df=307, p=0.117). Conclusions: The IHD intervention significantly improved respondents' knowledge of CC screening, highlighting its potential as an effective strategy for health education in rural communities. Awareness programs should prioritize engaging, interactive approaches to empower women with critical health information.